Life Dissatisfaction and Anxiety in COVID-19 pandemic - Pablo de Pedraza; Martin Guzi; Kea Tijdens (Global Labor Organization (GLO), 2020)
The rising numbers of COVID-19 cases and deaths, prolonged lockdowns, substantial restrictions on public life and an economic downturn negatively affect personal well-being. In this paper, we explore COVID- 19-related determinants of life dissatisfaction and feelings of anxiety using data collected from March 23 to April 30 2020 in 25 advanced and developing countries from four continents. We find that persons with better general health, with a paid job, living with a partner, daily exercising and those avoiding loneliness report less dissatisfaction and less anxiety. The presence of children and a pet in the household has no effect. Women report anxiety feelings more often than men. Older people report lower dissatisfaction and anxiety, remarkable given that the older population is among the most vulnerable in the current pandemic. Jobrelated changes due to COVID-19 such as income reduction and increase or decrease of workload are associated with more dissatisfaction and more anxiety. In reaction to the pandemic governments have adopted a range of measures. We show that restrictions on mobility and requirements to wear protective gear in public increase dissatisfaction and that the state-imposed emergency increase feelings of anxiety. We find that a growing number of confirmed COVID-19 cases increases dissatisfaction and anxiety but that this effect levels off with a higher number of cases. Our findings support targeted government policies to preserve economic security, and increase stability of employment.
Keywords: I31; I38; P51; D6; 330; Covid-19; life dissatisfaction; anxiety; public policy